Increased investment and enhanced partnerships towards low emissions development in livestock systems for East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
East African countries are strengthening efforts towards reducing GHG emissions from livestock. In Ethiopia, 7million USD investments from the Australian Centre for International Agricultural Research (ACIAR), Federal Ministry of Economic Cooperation and Development (BMZ) and World Bank mobilized towards this effort. This follows the 2018 workshop: "Low emissions livestock: Supporting policy-making and implementation through science in East Africa" organized by CCAFS, GRA, Food and Agriculture Organization (FAO), World Bank, African Climate Policy Centre (ACPC) and Ethiopian and New Zealand governments.